The relationship between autophagy and PD-L1 and their role in antitumor therapy - Cui, Yu; Shi, Jinfeng; Cui, Youbin; Zhu, Zhanpeng; Zhu, Wei (Frontiers in Immunology, 2023)
Immune checkpoint blockade therapy is an important advance in cancer treatment, and the representative drugs (PD-1/PD-L1 antibodies) have greatly improved clinical outcomes in various human cancers. However, since many patients still experience primary resistance, they do not respond to anti-PD1/PD-L1 therapy, and some responders also develop acquired resistance after an initial response. Therefore, combined therapy with anti-PD-1/PD-L1 immunotherapy may result in better efficacy than monotherapy. In tumorigenesis and tumor development processes, the mutual regulation of autophagy and tumor immune escape is an intrinsic factor of malignant tumor progression. Understanding the correlation between the tumor autophagy pathway and tumor immune escape may help identify new clinical cancer treatment strategies. Since both autophagy and immune escape of tumor cells occur in a relatively complex microenvironmental network, autophagy affects the immune-mediated killing of tumor cells and immune escape. Therefore, comprehensive treatment targeting autophagy and immune escape to achieve “immune normalization” may be an important direction for future research and development. The PD-1/PD-L1 pathway is essential in tumor immunotherapy. High expression of PD-L1 in different tumors is closely related to poor survival rates, prognoses, and treatment effects. Therefore, exploring the mechanism of PD-L1 expression is crucial to improve the efficacy of tumor immunotherapy. Here, we summarize the mechanism and mutual relationship between autophagy and PD-L1 in antitumor therapy, which may help enhance current antitumor immunotherapy approaches.